Impact of Asian Financial Stress on Indonesian Bank Credit Growth - Sahdan Saputra; Layali Ihyani (Universitas Airlangga, 2025)
Objective: This study aims to analyze the influence of the Financial Stress Index from Asian countries with high economic connectivity on the growth of bank credit in Indonesia, such as Singapore, China, Hong Kong, Japan, and Malaysia. Methods: Using time series data from the growth of general bank credit in Indonesia and the Financial Stress Index (FSI) from each country from January 2011 to August 2023, the total number of observations (N) in this study is 152. Therefore, this study uses the multiple linear regression method with the Ordinary Least Squares (OLS) approach. Findings: The findings reveal that the Financial Stress Index (FSI) from economically connected Asian countries does not significantly influence Indonesia’s bank credit growth. In contrast, domestic FSI shows a negative and significant effect, indicating that internal financial stress directly slows credit expansion and increases overall credit risk. The results also show that banks with larger asset sizes experience a greater reduction in credit growth, consistent with the negative impact of the SIZE variable. Additionally, higher operational costs (BOPO) further hinder credit growth, while increases in third-party funds (TPF) significantly enhance credit expansion and support lending capacity. Originality/Value: This study offers new evidence by showing that external financial stress from major Asian partners does not affect Indonesia’s credit growth, while domestic stress plays a decisive role. These findings expand the literature on financial spillovers by revealing Indonesia’s unique resilience compared to other emerging markets. Practical/Policy implication: These findings suggest that bank management should anticipate the Financial Stress Index (FSI) stemming from domestic sources by diversifying their credit portfolios. Meanwhile, regulators can formulate policies to mitigate the impact of external financial stress, such as macroprudential policies and regulations that encourage banks to increase their capital adequacy ratio during periods of economic stress.